Increased platelet aggregation and in vivo platelet activation after granulocyte colony-stimulating factor administration - Spiel, Alexander O.; Bartko, Johann; Schwameis, Michael; Firbas, Christa; Siller-Matula, Jolanta; Schuetz, Matthias; Weigl, Manuela; Jilma, Bernd (Thrombosis and Haemostasis, 2011)
Granulocyte colony-stimulating factor (G-CSF) stimulates the bone marrow to produce granulocytes and stem cells and is widely used to accelerate neutrophil recovery after chemotherapy. Interestingly, specific G-CSF receptors have been demonstrated not only on myeloid cells, but also on platelets. Data on the effects of G-CSF on platelet function are limited and partly conflicting. The objective of this study was to determine the effect of G-CSF on platelet aggregation and in vivo platelet activation. Seventy-eight, healthy volunteers were enrolled into this randomised, placebo-controlled trial. Subjects received 5 μg/kg methionyl human granulocyte colony-stimulating factor (r-metHuG-CSF, filgrastim) or placebo subcutaneously for four days. We determined platelet aggregation with a whole blood impedance aggregometer with various, clinically relevant platelet agonists (adenosine diphosphate [ADP], collagen, arachidonic acid [AA], ristocetin and thrombin receptor activating peptide 6 [TRAP]). Filgrastim injection significantly enhanced ADP (+40%), collagen (+60%) and AA (+75%) -induced platelet aggregation (all p<0.01 as compared to placebo and p<0.001 as compared to baseline). In addition, G-CSF enhanced ristocetin-induced platelet aggregation (+18%) whereas TRAP-induced platelet aggregation decreased slightly (-14%) in response to filgrastim. While baseline aggregation with all agonists was only slightly but insignificantly higher in women than in men, this sex difference was enhanced by G-CSF treatment, and became most pronounced for ADP after five days (p<0.001). Enhanced platelet aggregation translated into a 75% increase in platelet activation as measured by circulating soluble P-selectin. G-CSF enhances platelet aggregation and activation in humans. This may put patients suffering from cardiovascular disease and cancer at risk for thrombotic events.
Keywords: G-CSF; platelets; whole blood aggregometry; randomised controlled trial; gender difference